Intestinal barrier function, caecal microbiota and growth performance of thermoneutral or heat stressed broiler chickens fed reduced crude protein diets supplemented with guanidinoacetic acid - Reza Barekatain; Vivienne Inhuber; Nishchal Sharma; Tanya Nowland; Thi Thu Hao Van; Robert J. Moore; David Cadogan (Poultry Science)
The effectiveness of guanidinoacetic acid (GAA) in reduced protein (RP) diets on performance and gut health of broilers under heat stress is largely unknown. A 35-d experiment was conducted using four dietary treatments: a standard protein diet (SP, 22.1 and 20.7% CP in grower and finisher), a RP diet (20.1 and 18.7% in grower and finisher), a RP diet with 0.092% GAA per kg diet substituting 50% of supplemented arginine (GAA50) at one-to-one ratio and a RP diet with the same amount of GAA added on top (GAAtop). Day-old male Ross 308 chicks were assigned to 64 pens (10 birds each) in two rooms. In each room, each diet was replicated 8 times. From d 25 to 35, birds in one room were subjected to a cyclic heat stress (32±1 °C for 8 h). There was no interaction between diets and heat stress for any of the studied parameters. GAA50 followed by GAAtop significantly decreased the feed intake during the finisher phase (P<0.01) and from d 10 to 35 (P<0.001), compared with SP diet. Heat stress reduced (P<0.0001) feed intake and body weight gain at all stages of the study but did not impact FCR. The GAA50 tended to reduce FCR from d 24 to 35 (P=0.086) and d 10 to 35 (P=0.082) compared with SP and RP. Heat stress increased (P<0.05) intestinal permeability whereas diets had no effect. The gene expression of IL1β was downregulated (P<0.01) by GAA50 but diet had no effect on other selected genes. Heat stress upregulated the expression of several genes including Claudin 2, Claudin 3, GPX-1, HSP70, IL1β, SOD-1 and AMPK-α1. Caecal microbiota composition remained unaffected. The results indicate that replacing 50% of supplemented arginine with GAA tends to improve FCR by reducing the feed intake under both thermoneutral and heat stress conditions without any interaction. Supplementation of GAA or two percentage points reduction of dietary protein had no demonstrable effects on parameters of intestinal health.